Berge, Coppock, Maagerø (red.): Å skape mening med språk. En samling artikler av M.A.K. Halliday, R. Hasan og J.R. Martin. Oslo: Cappelen Akademisk Forlag as, 1998 - Askehave, Inger; Ditlevsen, Marianne Grove (HERMES - Journal of Language and Communication in Business, 2000)
The aim of this review article is to evaluate and discuss the above collection of syste-mic functional articles – translated into Norwegian and edited by Berge, Coppock and Maagerø. Furthermore, the article introduces the core concepts of SFL and provides an overview of the use of SFL in a Danish context.